Paradigms and Methods in Early Medieval Studies
XV, 257 p.
Keywords: The articles in this volume, by scholars all pursuing careers in the United States, concern the theoretical approaches and methods of early medieval studies. Most of the issues examined span the period from roughly 400 to 1000 CE and regions stretching from westernmost Eurasia to the Black Sea and the Baltic. This is the first volume of essays explicitly to reassess the heuristic structures and methodologies of research on "early medieval Europe." Because of its geographic, chronological, thematic, and methodological diversity and scope, the collection also showcases the breadth of early medieval studies currently practiced in the United States.